Oncogenes expand during evolution to withstand somatic amplification. (11th September 2018) - Wang, X; Li, X; Zhang, L; Wong, S H; Wang, M H T; Tse, G; Dai, R Z W; Nakatsu, G; Coker, O O; Chen, Z; Ko, H; Chan, J Y K; et al.
Abstract: Background: Cancer-related genes are under intense evolutionary pressure. We conjectured that gene size is an important determinant of amplification propensity for oncogenes and thus cancer susceptibility and therefore could be subject to natural selection. Patients and methods: Gene information, including size and genomic locations, of all protein-coding genes were downloaded from Ensembl (release 87). Quantification of gene amplification was based on Genomic Identification of Significant Targets in Cancer scores obtained from available The Cancer Genome Atlas studies. Results: Oncogenes are larger in size as compared with non-cancer genes (mean size: 92.1 kb versus 61.4 kb; P < 0.0001) in the human genome, which is contributed by both increased total exon size (mean size: 4.6 kb versus 3.4 kb; P < 0.0001) and higher intronic content (mean %: 84.8 versus 78.0; P < 0.01). Such non-random size distribution and intronic composition are conserved in mouse and Drosophila (all P < 0.0001). Stratification by gene age indicated that young oncogenes have been subject to a stronger evolutionary pressure for gene expansion than their non-cancer counterparts. Pan-cancer analysis demonstrated that larger oncogenes were amplified to a lesser extent. Tumor-suppressor genes also moved toward small oncogenes in the course of evolution. Conclusions: Oncogenes expand in size whereas tumor-suppressor genes move closer to small oncogenes in the course of evolution to withstand oncogenic somatic amplification. Our findings have shed new light on the previously unappreciated influence of gene size on oncogene amplification and elucidated how cancers have shaped our genome to its present configuration.